Implementation of Digital Media in Improving Higher Order Thinking Skills (Hots) in IPAS Subjects - Siti Anisatun Nafi'ah; Wahyu Hidayat; Rizki Agung Wijayati Hadi Safitri; Vidya Pandan Wangi (International Journal of Basic Educational Research, 2026)
Abstract The purpose of this study is to improve students' understanding in HOTS-based science learning on the material "Hearing Because of Sound". The type of research used in this study is Case Study and Field Observation. The development used in this study is the Classroom Action Research Model (CAR). Data collection techniques used in this study are interviews and tests. The data analysis techniques used are quantitative and qualitative data analysis techniques. The results of the study show that students have shown an increase in understanding of the material "Hearing Because of Sound" in the science subject. This can be seen based on the results of the pretest that has been carried out obtaining a "quite good" category with an average score of 78.1 which has increased through the results of the posttest that has been carried out which obtained "good" results with an average score of 81.5 out of a maximum score of 100 with a KKM of 75. This shows that HOTS-based science learning using digital media with the material "Hearing Because of Sound" can be applied because it has a positive influence on students' understanding and learning outcomes. Keywords: Science Learning, Hearing Because of Sound, HOTS.